Analysis of BRCT5 domain-containing proteins reveals a new component of DNA damage repair in Arabidopsis - Vladejić, Jovanka; Yang, Fen; Dvořák Tomaštíková, Eva; Doležel, Jaroslav; Palecek, Jan J.; Pecinka, Ales (Frontiers in Plant Science, 2022)
The integrity of plant genetic information is constantly challenged by various internal and external factors. Therefore, plants use a sophisticated molecular network to identify, signal and repair damaged DNA. Here, we report on the identification and analysis of four uncharacterized Arabidopsis BRCT5 DOMAIN CONTAINING PROTEINs (BCPs). Proteins with the BRCT5 domain are frequently involved in the maintenance of genome stability across eukaryotes. The screening for sensitivity to induced DNA damage identified BCP1 as the most interesting candidate. We show that BCP1 loss of function mutants are hypersensitive to various types of DNA damage and accumulate an increased number of dead cells in root apical meristems upon DNA damage. Analysis of publicly available sog1 transcriptomic and SOG1 genome-wide DNA binding data revealed that BCP1 is inducible by gamma radiation and is a direct target of this key DNA damage signaling transcription factor. Importantly, bcp1 plants showed a reduced frequency of somatic homologous recombination in response to both endogenous and induced DNA damage. Altogether, we identified a novel plant-specific DNA repair factor that acts downstream of SOG1 in homology-based repair.